Hubungan Kecemasan dengan Kesiapsiagaan Bencana Gempa Bumi pada Siswa SMAN 1 Cisarua yang Berlokasi di Zona Merah Sesar Lembang - Setiawati, Pipit Fitri; Kosasih, Cecep Eli; Sari, Sheizi Prista (Universitas Malahayati, 2025)
ABSTRACT Indonesia is a country with a high risk of disasters, including earthquakes. Preparedness is important to reduce the impact of disasters, while anxiety can influence preparedness by fostering motivation. The purpose of this study was to determine the relationship between anxiety and earthquake disaster preparedness among SMAN 1 Cisarua students located in the Red Zone of the Lembang Fault. This research is a quantitative research with a cross-sectional approach involving 95 students as respondents. The instruments used were the Indonesian version of the General Anxiety Disorder (GAD-7) questionnaire to measure anxiety and the LIPI-UNESCO/ISDR (2006) preparedness questionnaire to measure preparedness. The data of the research respondents were analyzed using Spearman rho non-parametric analysis. The results showed that most students had a moderate level of anxiety (58,9%) and a ready level of preparedness (60%). The p-value obtained is 0,013 and the correlation coefficient is 0,255 which indicates that there is a significant relationship between anxiety and earthquake disaster preparedness with a weak relationship strength and positive relationship direction. Anxiety with earthquake disaster preparedness has a positive relationship at a certain level, namely anxiety at a moderate level will contribute to increasing preparedness by fostering encouragement or motivation. Keywords: Anxiety, Disaster Preparedness, Earthquake, Student ABSTRAK Indonesia merupakan negara yang berisiko tinggi terhadap bencana, termasuk gempa bumi. Kesiapsiagaan penting untuk mengurangi dampak bencana, sedangkan kecemasan dapat memengaruhi kesiapsiagaan dengan menumbuhkan doroangan atau motivasi. Tujuan penelitian ini adalah untuk mengetahui hubungan kecemasan dengan kesiapsiagaan bencana gempa bumi pada siswa SMAN 1 Cisarua yang berlokasi di Zona Merah Sesar Lembang. Penelitian ini merupakan penelitian kuntitatif dengan pendekatan cross-sectional yang melibatkan 95 siswa sebagai responden. Instrumen yang digunakan adalah kuesioner General Anxiety Disorder (GAD-7) versi bahasa Indonesia untuk mengukur kecemasan dan kuesioner kesiapsiagaan LIPI-UNESCO/ISDR (2006) untuk mengukur kesiapsiagaan. Data responden penelitian dianalisis menggunakan analisis non-parametrik Spearman rho. Hasil penelitian menunjukkan jika sebagian besar siswa memiliki tingkat kecemasan sedang (58,9%) dan tingkat kesiapsiagaan siap (60%). Nilai p-value yang didapatkan sebesar 0,013 dan koefisien korelasi 0,255 yang mengindikasikan bahwa terdapat hubungan yang signifikan antara kecemasan dan kesiapsiagaan bencana gempa bumi dengan kekuatan hubungan yang lemah serta arah hubungan yang positif. Kecemasan dengan kesiapsiagaan bencana gempa bumi memiliki hubungan yang positif pada tingkat tertentu, yakni kecemasan pada tingkat sedang akan berkonstribusi dalam meningkatkan kesiapsiagaan dengan menumbuhkan dorongan atau motivasi. Kata Kunci: Kecemasan, Kesiapsiagaan, Gempa Bumi, Siswa